Flood Risk Indices Mapping of Lebak Regency, Banten Province - Maulana, Yovi; Purnaditya, Ngakan Putu; Wigati, Restu; Subekti, Subekti; Priyambodho, Bambang Adhi (Jurnal Fondasi, 2023)
Indonesia, as a developed country, has water-related disaster problems.Flood is one of them and it occurs in mostly province, includingBanten province. Lebak Regency as the region of Banten Province hashistory of flood occurrences. According to the Banten ProvincialBPBD (2021), among 2015-2020 period, twenty-nine flood eventsoccurred in Lebak Regency. The severest flood of that period occurredin 2020. A total 2389 residents’ homes and forty-five units of publicfacilities were damaged. Flood in Lebak regency historically alsoresulted in nine deaths, and two people were declared missing. Theobjective of this study is to be figuring out the flood risk profile andwhich districts have the highest risk in Lebak Regency by develop therisk indices map. Risk indices map informs the risk of flooding in eachsub-district, hence the policies taken can be delivered by the authorityproperly. The method used in this study used overlays based on PerkaBNPB No. 2 of 2012. This research obtains the map of the floodhazard, vulnerability, and capacity level that generates through QGIS.According to the results of the study, the risk index of Lebak district islow with three states. The sub-districts with the non-risk category areseven sub-districts with a percentage of 25%, while the sub-districtsthat fall into the slightly risky category are 10 sub-districts with apercentage of 35.7% and the sub-districts that are in the fairly riskycategory are 11 sub-districts with a percentage of 39.3%. These resultsgiven the conclusion that Lebak Regency is not considerable risk onhydrological flood events. Moderate level on vulnerability shouldgives note to the authorities to enhance the disaster resiliences.